Positive Accounting Theory In Predicting Accounting Choice (An Overview Of Adopted IFRS In PSAK 16 Research On The Audited Financial Statements) - Agustin Fadjareni (STAR, 2014)
Background of this study is the implementation of IFRS di Indonesia which is implemented since 2008. One of PSAK that have been adopted was PSAK 16. This PSAK was permited entity to choose one of the method of fair value or historical cost to measure the property, plant and equipment. The purpose of this study is to test if The Positive Accounting Theory can predict choices of fair value method or historical cost method . This study observed 52 financial statement of company that listed on BEI at 2009. Dependent variable that used in this study was firm size, institutional stock ownership, leverage, and industrial membership. Result of the study shows that the fourth variable wasn’t have significant result in explaining The PAT predicting accounting choice of those methods of property, plant and equipment measurement